A Journey in the Catalytic Synthesis of 3-Substituted 3-Aminooxindoles - Yu, Jin-Sheng; Zhou, Feng; Liu, Yun-Lin; Zhou, Jian (Synlett, 2015)
3-Substituted 3-aminooxindoles represent a type of privileged scaffold widely present in natural products and pharmaceutically active compounds. Thus, their efficient construction is of current interest. This account describes our efforts in the development of new strategies and reactions for facile access to this prominent framework.1 Introduction2 Nucleophilic Addition to Isatin Ketimines3 Direct Amination of 3-Substituted Oxindoles4 Substitution Reactions of 3-Hydroxyoxindoles5 Conclusion and Outlook
Keywords: 3-substituted 3-aminooxindoles; isatin ketimines; aminations; substitution reactions; nucleophilic additions